Model Peningkatan Kinerja Pemasaran dalam Konteks Adaptabilitas Lingkungan - Ahmad Lukman Arif; - Widodo (Universitas Muria Kudus, 2011)
This study examines the performance improvement of marketing in the context of environmental adaptability, which examined the effect of creativity programs entrepreneurial orientation and marketing performance and creativity to the performance of marketing programs both before and in the context of environmental adaptability. The respondents are the managers of SMEs who are members of the Organization Centra Industries (OCI) Sculpture and Carving in Center Industry Mulyoharjo Jepara. which amounts to 157. Given the limited number of population, sampling method with the census method, meaning the number of samples equal to the population of which amounted to 157. The study results indicate that 1). When oriented entrepreneurial SMEs, the marketing of higher performance. This means that performance improvements constructed by the orientation of entrepreneurial marketing with innovation indicators, dare to take risks and act proactively 2). If SMEs have the creativity of marketing programs, the higher the marketing performance. This means that marketing performance improvement constructed by the creativity of marketing programs with indicators of reference, the discussion of marketing programs and compliance programs. 3). If SMEs have entrepreneurial orientation, the higher the creativity of marketing programs. It means increased creativity of marketing programs built by entrepreneurial orientation to the indicators of innovation, daring to take risks and act proactively 4). Moderating environmental adaptability and creativity of entrepreneurial orientation on performance marketing programs pemasaran.Artinya high environmental adaptability will increase the influence of entrepreneurial orientation and creativity of the marketing program marketing performance